Efficiency and Labor Market Dynamics in a Model of Labor Selection - Sanjay K. Chugh; Christian Merkl (Institute for the Study of Labor (IZA), 2015)
This paper characterizes efficient labor-market allocations in a labor selection model. The model's crucial aspect is cross-sectional heterogeneity for new job contacts, which leads to an endogenous selection threshold for new hires. With cross-sectional dispersion calibrated to microeconomic data, 40 percent of empirically-relevant fluctuations in the job-finding rate arise, which contrasts with results in an efficient search and matching economy. The efficient selection model's results hold in partial and general equilibrium, as well as with sequential search.
Keywords: E24; E32; J20; 330; sequential search; hiring costs; labor market frictions; labor selection; labor market; efficiency; amplification